2016
DOI: 10.1111/jcmm.12828
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short‐chain acyl‐CoA dehydrogenase on cardiomyocyte apoptosis

Abstract: Short‐chain acyl‐CoA dehydrogenase (SCAD), a key enzyme of fatty acid β‐oxidation, plays an important role in cardiac hypertrophy. However, its effect on the cardiomyocyte apoptosis remains unknown. We aimed to determine the role of SCAD in tert‐butyl hydroperoxide (tBHP)‐induced cardiomyocyte apoptosis. The mRNA and protein expression of SCAD were significantly down‐regulated in the cardiomyocyte apoptosis model. Inhibition of SCAD with siRNA‐1186 significantly decreased SCAD expression, enzyme activity and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…It was reported that PPAR- α activation could decrease IR-induced liver, heart, and brain injury by suppressing inflammation, apoptosis, and lipid peroxidation [ 41 , 42 ]. Furthermore, PPAR- α can promote the expression of Bcl-2 and subsequently inactivate apoptosis [ 43 ]. An experimental study suggested that fenofibrate could inhibit apoptosis through SIRT1-mediated deacetylation of FoxO1 [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that PPAR- α activation could decrease IR-induced liver, heart, and brain injury by suppressing inflammation, apoptosis, and lipid peroxidation [ 41 , 42 ]. Furthermore, PPAR- α can promote the expression of Bcl-2 and subsequently inactivate apoptosis [ 43 ]. An experimental study suggested that fenofibrate could inhibit apoptosis through SIRT1-mediated deacetylation of FoxO1 [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that SCAD expression was decreased in a cardiomyocyte apoptotic model [26]. Here, SCAD downregulation occurred in both tBHP-treated HUVECs and the human artery endothelial cell line HTX2397 apoptotic model and the oscillatory shear stress model, which imitated hypertensive stress.…”
Section: Discussionmentioning
confidence: 67%
“…Transfection Reagent (Beyotime Biotechnology, Co., Ltd, Shanghai, China) according to the manufacturer's instructions, cultured in normal Dulbecco's modified Eagle's medium (DMEM) and then treated with riboflavin and tBHP. The SCAD and DJ-1 oligonucleotide duplex sequences were separately based on previous studies (W. Li, Li, Leng, et al, 2020;Zeng et al, 2016).…”
Section: Scad and Dj-1 Knockdown By Small-interfering Rna (Sirna)mentioning
confidence: 99%
“…For the first time, our previous studies found that SCAD expression was decreased in pathological cardiac hypertrophy, heart failure and cardiomyocyte apoptosis. SCAD is a negative regulatory factor of heart failure (J. Huang, Xu, et al, 2015; Q. Huang, Huang, et al, 2015; Zeng et al, 2016). Interestingly, mitochondrial proteome analysis showed that DJ‐1 was down‐regulated in SCAD deficiency patients (Pedersen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%